Enhancing biocompatibility of PCL/PU nano-structures to control the water wettability by NaOH hydrolysis treatment for tissue engineering applications. Issue 2 (June 2022) - Jirofti, Nafiseh; Mohebbi-Kalhori, Davod; Masoumi, Ramin
Nano-structures due to their unique properties can provide a biomimetic structure for cell attachment and proliferation in tissue engineering (TE) applications. But sometimes, their surface properties are not particularly suitable for directed tissue growth. In this regard, present study has focused on fabrication and hydrolysis of Poly ( ε -caprolactone) (PCL)/Polyurethane (PU) by aqueous sodium hydroxide (NaOH) with a view to modify the surface and hydrophilicity of the structures. The characterizations and mechanical properties of non-hydrolyzed and hydrolyzed nano-structures were evaluated by SEM, FESEM, FTIR, water contact angle and tensile stress. The all hydrolyzed nano-structures showed improvement in contact angle after 2h at all concentrations of NaOH. The PCL, PU, PCL75%:PU25%, and PCL25%:PU75% structures have shown 3.8%, 12.5%, 4.1% and 7%, respectively, of shrinkage at hydrolysis at 3 M NaOH and 3 h. The PCL25%:PU75% structure indicated the greatest reduction in stress and strain at 3 M NaOH and 3 h (1.1 ± 0.06 MPa with 52% decreases) and (156 ± 5% with 49% decreases), respectively. Also, the structure with 75% of PCL showed 28% reduction in Young's Modulus (4.33 ± 0.45 MPa) at 3 M NaOH after 2 h. It is noted that the hydrolysis treatment with 3 M of NaOH concentration at 2 h is optimum condition for hydrolysis hybrid nan-structures for TE applications. Also, the results of this study proposed that hydrolyzed PCL75%:PU25% hybrid nano-structures due to its unique mechanical properties and optimum surface modification could be promising candidate for TE applications.